Designing Climate-Adaptive Buildings: Impact of Courtyard Geometry on Microclimates in Hot, Dry Environments - Muna Salameh; Basim Touqan (Civil Engineering Journal, 2024)
Designing climate-adaptive buildings is crucial for mitigating the adverse effects of climate change by enhancing energy efficiency and reducing greenhouse gas emissions. Additionally, such designs improve thermal comfort and resilience in urban environments, particularly in regions with extreme climates, thereby promoting sustainable living conditions. This study aims to mitigate climate change through strategic urban and building design, focusing on the impact of building geometry and courtyard configurations on enhancing microclimates and thermal comfort in the UAE's hot arid climate. Utilizing ENVI-met software for qualitative analysis, the research examines design modifications in a school building's layout and courtyards. The analysis and findings reveal that strategic alterations can reduce outdoor air temperatures by up to 1.45°C and average building temperatures by approximately 1.89°C. Additionally, these modifications significantly improve thermal comfort perceptions on the PMV scale. The findings underscore the potential of architectural design to contribute to climate change mitigation efforts, highlighting the importance of thoughtful building and courtyard designs in promoting sustainable architecture and urban planning. This study offers novel insights into the role of design in enhancing thermal environments, providing a practical approach for developing climate-adaptive buildings in hot, dry environments. Doi: 10.28991/CEJ-2024-010-08-017 Full Text: PDF